Abu Gharib a torture's tale - Films for the Humanities and Sciences (New Jersey : Films for the Humanities and Sciences, 2006)
Javal Davis was imprisoned for assaulting inmates at Abu Ghraib, but insists he is not a torturer. His fellow MP Ken Davis was never implicated, having reported the abuse to superiors. This program presents in-depth interviews with both men, detailing their side of the story and conveying their disillusionment with Pentagon officials who wanted interrogations pushed'up a notch'
Title from title screen
DVD format
Keywords: Abu Ghraib Prison; Iraq War, 2003- -- Prisoners and prisons, American